Clinical Efficacy of Intravenous Papaverine plus Ketorolac in the Emergency Treatment of Renal Colic: A Letter to the Editor: The Authors’ Reply - Ali Khavanin; Javad Mozafari; Samaneh Porozan; Mohammadghasem Hanafi (Iranian Journal of Medical Sciences)
We would like to address the letter critiquing our article entitled “Clinical Efficacy of Intravenous Papaverine Plus Ketorolac in the Emergency Treatment of Renal Colic: A Randomized, Double-blind Clinical Trial”, which was published in your esteemed journal (Vol 49, No. 11, November 2024). We appreciate the thoughtful comments provided in the letter and are grateful for the opportunity to respond to the points raised.